Redescrição dos tipos de veronicellidae (Mollusca, Gastropoda) neotropicais: VIII. Espécies depositadas no "Institut für Spezielle Zoologie und Zoologisches Museum" de Berlim, Alemanha Oriental - Thomé, José Willibaldo (Arquivos de Zoologia, 1972)
Upon examination of the types deposited in the Institut für Spezielle Zoologie und Zoologisches Museum, Berlin, DDR, 27 species of neotropical Veronteellidae are redescribed, Redescription is based on some new characters of external and internal morphology.